Optimization of Supercritical Carbon Dioxide Extraction of Saussurea costus Oil and Its Antimicrobial, Antioxidant, and Anticancer Activities - Hanaa Y. Ahmed; Sayed M. Kareem; Ahmed Atef; Nesreen A. Safwat; Reda M. Shehata; Mohammed Yosri; Mahmoud Youssef; Morooj M. Baakdah; Rokayya Sami; Roua S. Baty; Nouf H. Alsubhi; Ghadeer I. Alrefaei; et al. (MDPI AG, 2022)
Saussurea costus is a medicinal plant with different bioactive compounds that have an essential role in biomedicine applications, especially in Arab nations. However, traditional extraction methods for oils can lead to the loss of some volatile and non-volatile oils. Therefore, this study aimed to optimize the supercritical fluid extraction (SFE) of oils from S. costus at pressures (10, 20, and 48 MPa). The results were investigated by GC/MS analysis. MTT, DPPH, and agar diffusion methods assessed the extracted oils' anticancer, antioxidant, and antimicrobial action. GC/MS results showed that elevated pressure from 10 to 20 and 48 MPa led to the loss of some valuable compounds. In addition, the best IC50 values were recorded at 10 MPa on HCT, MCF-7, and HepG-2 cells at about 0.44, 0.46, and 0.74 μg/mL, respectively. In contrast, at 20 MPa, the IC50 values were about 2.33, 6.59, and 19.0 μg/mL, respectively, on HCT, MCF-7, and HepG-2 cells, followed by 48 MPa, about 36.02, 59.5, and 96.9 μg/mL. The oil extract at a pressure of 10 MPa contained much more of á-elemene, dihydro-à-ionone, patchoulene, á-maaliene, à-selinene, (-)-spathulenol, cedran-diol, 8S,13, elemol, eremanthin, á-guaiene, eudesmol, ç-gurjunenepoxide-(2), iso-velleral, and propanedioic acid and had a higher antioxidant activity (IC50 14.4 μg/mL) more than the oil extract at 20 and 48 MPa. In addition, the inhibitory activity of all extracts was higher than gentamicin against all tested bacteria. One of the more significant findings from this study is low pressure in SFE enhancement, the extraction of oils from S. costus, for the first time. As a result, the SFE is regarded as a good extraction technique since it is both quick and ecologically friendly. Furthermore, SFE at 10 MPa increased the production and quality of oils, with high antioxidant activity and a positive effect on cancer cells and pathogens.